Pronounced Plastic and Evolutionary Responses to Unpredictable Thermal Fluctuations in Drosophila simulans - Sørensen, Jesper G.; Manenti, Tommaso; Bechsgaard, Jesper S.; Schou, Mads F.; Kristensen, Torsten N.; Loeschcke, Volker (Frontiers in Genetics, 2020)
Organisms are exposed to temperatures that vary on diurnal and seasonal scales. Thus, the ability to behaviorally, physiologically or evolutionary respond to variation in temperatures is a fundamental requirement for long-term persistence. Studies on thermal adaptations in ectotherms are typically performed under constant and well-controlled laboratory conditions which differ markedly from the variation in temperature across time and space in the wild. Here, we investigate evolutionary and plastic responses of D. simulans to constant temperature as well as to predictable or unpredictable thermal fluctuations. We sequenced populations exposed to 20 generations of experimental evolution under the three thermal regimes and examined the proteome after short-term exposure to the three regimes. We find that unpredictable fluctuations cause the strongest response at both genome and proteome levels. The evolutionary response, i.e. regions under selection, did not coincide with induced responses of the proteome. Thus, genes under selection in fluctuating thermal environments are distinct from genes important for the adaptive plastic response observed within generations. The genes under selection is also distinct from previously identified loci that showed evolutionary responses at the expression level. We suggest that genomic changes in trans-regulatory elements cause the responses identified at the proteome and expression levels. This information is key to obtain a better understanding, interpretation, and prediction of the potential effects of climate change that are causing increases in both mean and variability of temperatures.